Spatial interference scale as a determinant of microbial range expansion - Ozgen, Venhar Celik; Kong, Wentao; Blanchard, Andrew E.; Liu, Feng; Lu, Ting (Amer Assoc Advancement Science, 2018)
In microbial communities, social interactions such as competition occur ubiquitously across multiple spatial scales from local proximity to remote distance. However, it remains unclear how such a spatial variation of interaction contributes to the structural development of microbial populations. Here, we developed synthetic consortia, biophysical theory, and simulations to elucidate the role of spatial interference scale in governing ecosystem organization during range expansion. For consortia with unidirectional interference, we discovered that, at growing fronts, the extinction time of toxin-sensitive species is reciprocal to the spatial interference scale. In contrast, for communities with bidirectional interference, their structures diverge into distinct monoculture colonies under different initial conditions, with the corresponding separatrix set by the spatial scale of interference. Near the separatrix, ecosystem development becomes noise-driven and yields opposite structures. Our results establish spatial interaction scale as a key determinant for microbial range expansion, providing insights into microbial spatial organization and synthetic ecosystem engineering.
Keywords: Gene-Expression; Cooperation; Biofilms; Communication; Competition; Dispersal; Dynamics; Pattern; Protein; Growth